Uptake of cationized albumin coupled liposomes by cultured porcine brain microvessel endothelial cells and intact brain capillaries - Thöle, Marc; Nobmann, Stephanie; Fricker, Gert (Journal of drug targeting, 2002)
The suitability of protein-coupled liposomes as drug carriers for brain specific targeting was investigated using albumin (BSA) and cationized albumin (CBSA), respectively, as model proteins. Liposomes coated with polyethylene glycol (sterically stabilized, PEG-liposomes) were prepared from phosphatidylcholine, cholesterol, and a PEG-derivatized phospholipid and covalently coupled to thiolated BSA or CBSA. Liposomes were loaded with carboxy-fluorescein and rhodamine-labeled dipalmitoyl-phosphatidylethanolamine as hydrophilic and lipophilic marker compounds, respectively. The interaction of these constructs with monolayers of porcine brain capillary endothelial cells (BCEC) and freshly isolated porcine brain capillaries was studied by means of fluorescence assays and confocal laser scanning fluorescence microscopy (CLSFM). In contrast to BSA, CBSA was rapidly taken up by cultured BCECs. BSA-coupled liposomes did not interact with endothelial cells, whereas CBSA-coupled liposomes bound to cellular surfaces and exhibited time dependently a high intracellular accumulation. CBSA-conjugated liposomes were also taken up by intact brain capillaries. Cellular uptake could be inhibited by free cationized albumin, phenylarsineoxide, nocodazole, and filipin, but not by dansylcadaverine, suggesting a caveolae-mediated incorporation process. Immunostaining demonstrated a high expression of caveolin in the capillary endothelium. In conclusion, liposomes coupled to CBSA are taken up into brain endothelium via an endocytotic pathway and may therefore be a suitable carrier for drug delivery to the brain.
Gesehen am 25.04.2017